Machine Learning: TCO‐Based Active Dielectric Metasurfaces Design by Conditional Generative Adversarial Networks (Adv. Theory Simul. 2/2021). Issue 2 (4th February 2021) - Jafar‐Zanjani, Samad; Salary, Mohammad Mahdi; Huynh, Dat; Elhamifar, Ehsan; Mosallaei, Hossein
Abstract : In article 2000196, Hossein Mosallaei and co‐workers propose a machine learning (ML) method for broad‐band multi‐modal inverse design of TCO‐based active metasurfaces. Their proposed technique is a combination of a K‐means clustering algorithm and conditional generative adversarial networks (cGANs). It casts light on how ML models can solve inverse‐design problems and the level of intelligence they can provide.